Pengaruh Pengalaman Berorganisasi dan Pengalaman Kerja Part-Time terhadap Kesiapan Kerja Mahasiswa Universitas Teuku Umar - Isnawati Isnawati; Hamdi Harmen; Nabila Hilmy Zhafira (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of organizational experience and part-time work experience on work readiness among students of Universitas Teuku Umar. A quantitative correlational approach was employed with a population of students who have organizational and part-time work experience. The sample consisted of 107 respondents selected using purposive sampling. Data were collected through a closed-ended questionnaire with a Likert scale of 1–5 and analyzed using multiple linear regression through SPSS version 25, preceded by validity, reliability, and classical assumption tests. The results indicate that partially, organizational experience (X₁) has a positive and significant effect on work readiness (Y) with t-value of 7.410 > t-table 1.983 (sig. 0.000 < 0.05), and part-time work experience (X₂) also has a positive and significant effect with t-value of 5.109 > t-table 1.983 (sig. 0.000 < 0.05). Simultaneously, both variables have a significant effect on work readiness with F-value of 71.488 > F-table 3.08 (sig. 0.000 < 0.05). The R Square value of 0.579 indicates that both variables explain 57.9% of the variation in work readiness, while the remaining 42.1% is explained by other variables outside the study. Students are expected to be more active in organizational activities and utilize part-time work experience to enhance skills and readiness for the workforce.